Handbook of gynecological emergencies - Rao, Kamini A. (Jaypee Brothers Medical Publishers, 2015)
Practical guide to gynaecological emergencies with emphasis on accurate patient assessment. Covers diagnosis and treatment of emergencies in different age groups.